Religious Guidance and Character Education for School Dropouts at the Social Rehabilitation Center - Basyiroh, Basyiroh (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the implementation of religious guidance at the Social Rehabilitation Center. Methodology: This study uses a qualitative approach with 12 respondents as research subjects. The interview method is the main method and the documentation method is complementary. The data collection method is carried out using a research instrument in the form of an interview, namely an interview with questions regarding the implementation of religious guidance. While the documentation method is used to determine the location and subject of the study. Main Findings: The research results obtained show that religious development activities include: recitation (study of Fiqh), mujahadah and al-Qur'an, learning about read and write the Quran, yasinan and tahlil at regular recitation, tadarus Al-Qur'an. The methods used in implementing coaching are: lecture, question and answer, habituation and example methods and every time coaching is completed, the coach always conducts an evaluation. The aim of implementing religious coaching is so that the beneficiaries are to direct teenagers about the importance of knowledge about religion and have the awareness to carry it out. So that it is useful in this world and in the afterlife. Novelty/Originality of this study: This study opens up new insights into the importance of integrating religious guidance with character education in restoring the learning spirit and morals of school dropouts at the Social Rehabilitation Center.